(untitled) (Innovative professional education, 2025)
The article examines the methods of integrating and applying a Learning Management System (LMS) on digital platforms for the professional training of qualified workers in the machine-building industry. In the context of education digitalization, innovative technologies enhance the learning process’s efficiency by providing access to interactive tools, flexible educational materials, and personalized assessment approaches.